Utilization of Pili (Canarium ovatum) sawdust in bio-crude oil production and the identification of potential by-products through thermochemical conversion - Prado, Jerico; Mendez, Jean Claude; Brillante, Florelyn; Ocampo, Darrel (Acta Chimica Asiana, 2024)
This study aimed to utilize Pili sawdust in the production of bio-crude oil and identify its potential by-products through thermochemical conversion. To obtain all the essential data, this research sought to answer the questions: (1) How much bio-crude oil can be produced at constant factors such as temperature and amount of Pili (Canarium ovatum) sawdust? (2) What are the physical characteristics of the generated bio-crude oil after conducting thermochemical conversion? (a) Color, (b) Appearance, and (c) Viscosity (3) What other potential by-product can be generated out of Pili (Canarium ovatum) sawdust after conducting thermochemical conversion. (4) What are the physical characteristics of the generated by-products after conducting thermochemical conversion? (a) Color and (b) Appearance. Experimental-descriptive method was used in perceiving the physical properties of the by-products and its bio-crude oil production, presented in milliliters (mL) and to be expressed in percentage respectively.  Based on the gathered observation record results, data revealed that 1000 g of Pili sawdust in 340 oC temperature, yields 30% or 300mL of brownish bio-crude oil in color, with a high degree of viscosity. Consequently, the generated by-products are biochar and synthesized biogas. The 242.2g of biochar which yields 24.52%, resulted being porous and coarse-grained in texture. While the synthesized biogas generated 433.4g of net weight yields 43.34%, resulted in having a high flammability. For the betterment of similar study, future researchers are encouraged to evaluate the agricultural potential of the generated biochar and to distillate bio-crude oil for possible commercial use.